A Descriptive Review of Cannabis sativa Patents for Cancer Treatment - Pereira, Isabela F.; Santos Oliveira, Ana Maria; Santos, Anamaria Mendonça; de Melo Soares, Denis; Serafini, Mairim Russo; Almeida Alves, Izabel (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Background: Cannabis use for tumor treatment has been explored in several areas, and its potential for tumor remission is currently being studied after the discovery of the endogenous cannabinoid.Objective: The study aimed to conduct a critical patent review to identify and explore the latest advances and therapeutic strategies using Cannabis to treat cancer.Methods: The research was carried out in the free and online database Espacenet, using the descriptors
Keywords: Cancer